Decir lo normal. Reflexiones en torno al trasfondo ético del lenguaje de la psiquiatría - Maruy van den Broek, Rodrigo (Pontificia Universidad Católica del Perú. Instituto Riva-Agüero, 2019)
This article aims to rethink the ethical dimensions of the psychiatric diagnosis as a speech act. Thereupon, we will explore the internal tensions of the psychiatric language in light of Kant’s distinction between determining and reflective judgements. Then, we shall emphasize the performative dimension of the diagnosis from the perspectives of Austin and Wittgenstein, thus problematizing the idea that it is an objective description of the patient’s abnormality. Finally, in dialogue with the epistemic injustice approach, we will propose a commissive notion of diagnosis that can also serve as a means for social criticism.

Este texto se propone repensar las dimensiones éticas del diagnóstico psiquiátrico en tanto acto de habla. Para ello, exploraremos las tensiones internas al lenguaje de la psiquiatría desde la distinción kantiana entre juicios determinantes y reflexionantes. Luego, enfatizaremos la dimensión performativa del diagnóstico desde Austin y Wittgenstein, problematizando la idea de que este es una descripción objetiva de la anormalidad del paciente. Por último, en diálogo con el enfoque de la injusticia epistémica, propondremos una noción compromisoria de diagnóstico que pueda desempeñarse como un medio de crítica social.
Keywords: Diagnóstico; Psiquiatría; Acto de Habla; Injusticia Epistémica; Crítica Social; https://purl.org/pe-repo/ocde/ford#6.03.01